Design and development of a seeding machine for system of rice intensification seedling tray - Abdulkadir, Tukur Daiyabu (2019)
The manual seeding of the system of rice intensification (SRI) seedling tray is labor and time intensive, therefore, there is need to have a machine for the seeding process. In this study a seeding machine for SRI seedling tray was designed, developed and evaluated. The use of vacuum suction as a tool for single seeding of paddy seed to SRI seedling tray was conceived. The amount of vacuum pressure required for single seeding of MR219 paddy seed was determined using existing models and evaluated experimentally. Cone angle and seed-hole diameter as important nozzle parameters were determined and evaluated experimentally. A vacuum seeding manifold with 924 seeding nozzles was proposed for the SRI seedling tray seeding process. Computational fluid dynamic (CFD) software was used to optimize the manifold design, where the effect of number of suction outlets on vacuum pressure uniformity was investigated. The effect of vacuum chamber type on vacuum pressure distribution uniformity was also investigated, where two manifold types with cylindrical and rectangular vacuum chambers were compared using CFD. Two types of pick and place mechanisms, which are screw mechanism and crank rocker mechanism, were proposed and compared analytically for best performance in terms of operational speed. The strength of the links of the crank-rocker pick and place mechanism was simulated using finite element analysis (FEA). The flow property of seedling growing media in relation to hopper material surface was studied using Jenike’s procedure, where the optimum hopper angle was determined for development of seedling media hopper. A seeding machine was developed for SRI seedling tray. The machine consists of three basic sub systems synchronized to work as a single unit, these are: media placement system that place planting media to the seedling cavities before and after seed placement; seed placement system that place single seed per seedling cavity; and tray conveying systems that transport the seedling tray from beginning to the end of the seeding process. In operation, one operator places a seedling tray on the conveyor at one end of the seeding machine. The conveyor transports it to pass below a media hopper. A first layer of media is sprayed on the tray. When the tray reaches seed placement section, an object detection sensor detects its presence and stops the conveyor. The seed placement mechanism picks the seeds from a seed tray and places them into the seedling cavities with the aid of vacuum suction and solenoid valve. The tray is then transported to pass below a second media hopper where the seeds are covered. A third operator removes the seeded tray from the conveyor. The machine performance was evaluated based on media placement and single seeding capability. The amount of vacuum for single seeding of MR219 seeds was found to be between 18.3 and 29.15 mbar. Experimental evaluation of this vacuum pressure has shown that the optimum vacuum pressure for single seeding of paddy seed is 30 mbar. The optimum seed-hole diameter was found to be 1 mm and was adopted for the seeding manifold development. The effect of number of suction outlets on vacuum pressure distribution uniformity was not significant. For seeding manifold with 924 seeding nozzles, manifold with rectangular vacuum chamber type was found to have a better pressure distribution uniformity than manifold with cylindrical vacuum chamber type. Crank-rocker mechanism with a theoretical operational period of 1 second per pick and place circle was found to have a better performance than the screw mechanism with 78.8 second per pick and place circle. A safety of factor of 4.64 ul was obtained from the FEA analysis for mechanism links. The hopper angle for mass flow of planting media was found to be 22ᵒ. The evaluation results of the seed placement mechanism have shown that seeding without seed tray vibration has a better performance, where the best performance of 75% single seeding, 0% multiple seeding and 25% miss seeding was achieved. The results of evaluation with vibrating seed tray have shown a top performance of 46% single seeding, 0% multiple seeding and 54% missed seeding. A mean media depth of 18.32 mm was achieved. The field capacity and efficiency of the machine were found to be 1 tray/14 s (1 ha/ 0.67 hour) and 61.43% respectively.